Traditional Sundanese Games as Community-Based Learning Media for Interreligious Tolerance: A Qualitative Case Study at Sakola Motekar, West Java, Indonesia - Herdiansyah, Gymnastiar; Halim, Ilim Abdul; Busro, Busro (UIN Sunan Gunung Djati Bandung, 2025)
Purpose: This study examines how traditional Sundanese games function as a medium for interreligious tolerance among children within a community-based learning setting at Sakola Motekar. It addresses the growing concern over intolerance by exploring local cultural practices that enable children from different religious backgrounds to interact inclusively in everyday social spaces beyond formal schooling. Methodology: The study employs a qualitative single-case study design focused on the “Kaulinan” (traditional play) program at Sakola Motekar. Data were collected through participatory observation of recurring game sessions, in-depth semi-structured interviews with child participants and adult stakeholders. Findings: The findings show that the games were implemented as routinely facilitated activities embedded in weekly/outdoor sessions rather than purely child-initiated recreation. Across the three games, tolerance was enacted as observable interaction routines: children consistently participated in non-segregated groupings through shared formations, mixed teams, and turn-taking structures; cooperation toward shared goals was strengthened by game mechanics requiring task interdependence (maintaining an intact line, rebuilding a stack under pressure, or practicing balance with peer assistance); supportive peer responses (reassurance, encouragement, and practical help) were common when minor setbacks occurred; and rule disagreements were brief and typically resolved through quick negotiation supported by light-touch facilitator reminders, allowing play to continue without disrupting cohesion. Implications: The study suggests that facilitated traditional play can operate as a practical interaction infrastructure for tolerance education, where values emerge through repeated embodied practice rather than primarily through verbal instruction. Programmatically, the findings support the adoption of minimal facilitation standards to sustain inclusive participation and physical safety in community-based settings. Originality/Value: This research contributes naturalistic evidence from a community-based learning context showing how tolerance is produced as an everyday interactional accomplishment (grouping, cooperation, reassurance, and rule negotiation) rather than being treated mainly as a declarative attitude. It also offers multi-source qualitative support demonstrating how traditional games can function as cultural “media” (McLuhan) and experiential learning cycles (Kolb) that extend children’s social capacities in pluralistic settings.